Step by step approach for qualitative data analysis (International Journal of Built Environment and Sustainability, 2018)
The application of qualitative techniques is increasing and acceptable among the researchers. However, majority of the researchers and postgraduate students did not consider the importance of giving detailed procedures in qualitative data analysis for better understanding of the qualitative results. There is a need to uncover step by step approach in qualitative analysis for better application of qualitative techniques. This article presented a detailed step-by-step approach for qualitative analysis with the aid of a pragmatic illustration. The analytic process presented employed the example of qualitative data transcribed into narrative data to develop basic themes. The employment of Domain Analysis and Thematic Network analysis in the example given helped basic themes to converge to higher order themes. The article submitted that this approach in qualitative analysis will aid thorough understanding of qualitative data interpretation. This is extremely thoughtful approach for the systematic presentation of qualitative analysis.
Keywords: Domain Analysis; Qualitative Analysis; Qualitative Data; Qualitative Techniques; Thematic Network .